Insights into correlations between H. pylori infection and chronic hepatitis C disease progression: A Comparative study in the Egyptian population - Ragab, Ahmed; Elbrolosy, Asmaa M; Elabd, Naglaa S; Elgamal, Ayman; Rizk, Mahmoud; Nada, Ali; Omar, Marwa M; Eleowa, Sama S; Hamam, Sanaa S; Elmaghraby, Amira S (The Journal of Infection in Developing Countries, 2025)
Background: Accumulating evidence implicated H. pylori infection in the disease progression of patients with chronic liver. Highly virulent H. pylori mediate proinflammatory cytokines and ensuing inflammatory alterations. We aimed to assess the correlation between H. pylori infection and disease progression in chronic hepatitis C (HCV) patients with special concern on virulence traits and susceptibility patterns of isolated H. pylori strains. Methods: After clinical, laboratory, and radiological evaluations, 189 chronic HCV patients were assigned into Group I (74 patients with chronic HCV), Group II (77 cirrhotic patients), and Group III (38 hepatocellular carcinoma (HCC) patients on top of cirrhosis). Fecal samples were analyzed using ELISA to detect H. pylori antigens. Upper gastrointestinal (GIT) gastric biopsies were processed to identify and isolate H. pylori strains. PCR assay verified cagA, VacAs1 & VacAs2 gens in isolated strains to be correlated with the degree of hepatic disease. Results: H. pylori Ag in stool was identified in 73.02% of studied patients. H. pylori Ag was 55.4%, 84.4%, and 84.2% (p < 0.001); additionally, culture yielded viable H. pylori bacilli in 31.1%, 44.2%, and 55.3% (p = 0.039), and PCR assay revealed 47.8%, 85.3%, and 85.7% (p = 0.004) were positive for cagA and/or vacAs2 virulence genes in chronic hepatitis, cirrhosis, and HCC patients, respectively. The presence of H. pylori positive culture and/or genetic profile is associated with advanced-stage liver disease, hepatic encephalopathy, and portal hypertensive gastropathy. Conclusions: H. pylori infection should be assessed in all patients with liver impairment. Early H. pylori detection and subsequent eradication may lessen the severity of decompensation.